Emergency management of necrotic rectal prolapse in a domestic cat - Bermani , Fadeli; Septiyani (ARSHI Veterinary Letters, 2025)
A case of rectal prolapse in a domestic cat was treated at Veterinary Teaching Hospital, Universitas Padjadjaran, Indonesia. The cat presented with a six-day history of a reddish mass protruding from the anus. Physical examination revealed a prolapsed rectum with areas of necrosis, pale mucous membranes, and decreased skin turgor, which was consistent with dehydration. The fecal examination was negative for gastrointestinal parasites. The cat was diagnosed with complete rectal prolapse and associated tissue necrosis. The treatment consisted of manual reduction of the prolapsed rectum and placement of a purse-string suture to retain the rectum. The cat received broad-spectrum antibiotic therapy (amoxicillin (10 mg/kg) and metronidazole (25 mg/kg) during recovery, along with Tolfedine (4 mg/kg) for NSAID therapy. The purse-string suture was removed five days later, and no recurrence at one-month follow-up. This case illustrates the need for early diagnosis and timely surgical intervention in the management of rectal prolapse and to prevent progression to irreversible necrosis.